Analysis of the Role of Information Technology in Public Administration Transformation - Virendra, Alauddin Zuhdi; Hauzan, Emyr Choudhary; Abbad, Jiyad Umar (IHSA Institute, 2025)
This research explores the transformative role of information technology (IT) in public administration, examining its impact on service delivery, transparency, and citizen engagement. With the increasing demand for efficient governance in a rapidly evolving digital landscape, this study investigates how IT integration can enhance public sector operations and improve interactions between government institutions and citizens. Employing a mixed-methods approach, the research analyzes existing literature, case studies, and empirical data to identify best practices for IT adoption and implementation in public administration. Key findings indicate that successful IT integration leads to streamlined processes, increased accountability, and improved access to services. However, significant challenges remain, including insufficient infrastructure, resistance to change, limited digital literacy, and data privacy concerns. The research offers practical recommendations for overcoming these barriers, emphasizing the importance of fostering a culture of innovation, investing in training, and developing robust data governance frameworks. Ultimately, the study highlights the ongoing potential of IT to reshape public administration, suggesting that effective digital transformation is essential for building a more inclusive, responsive, and effective governance framework in the digital age.